Ultra‐performance liquid chromatography–tandem mass spectrometric assay for the simultaneous determination of brucine, strychnine and brucine N‐oxide in rat plasma: application to a pharmacokinetic study. (4th January 2016) - Gu, Wei; Wang, Dongyue; Pan, Zihao; Liu, Xiao; Cai, Baochang; Chen, Jun
Abstract: A rapid, simple and sensitive UHPLC‐MS/MS method was developed and validated for the simultaneous determination of brucine, strychnine and brucine N ‐oxide in rat plasma using huperzine A as an internal standard (IS) after protein precipitation with methanol. The analytes were separated on a Purospher® STAR RP18 UHPLC column (2 µm, 2.1 × 100 mm) by gradient elution using a mobile phase composed of methanol and water (containing 0.1% formic acid) at a flow rate of 0.3 mL/min. Brucine, strychnine, brucine N ‐oxide and IS were detected in positive ion multiple reaction monitoring mode by means of an electrospray ionization interface ( m / z 395.2 → 324.1, m / z 335.2 → 184.1, m / z 411.2 → 394.2, m / z 243.1 → 226.1). The calibration curve was linear over the range of 1–500 ng/mL for brucine and strychnine and 0.2−50 ng/mL for brucine N ‐oxide. The intra‐ and inter‐day precisions of these analytes were all within 15% and the accuracy ranged from 85 to 115%. The stability experiment indicated that the plasma samples at three concentration levels were stable under different conditions. The developed method was successfully applied for the first time to pharmacokinetic studies of brucine, strychnine and brucine N ‐oxide following a single oral and intravenous administration of modified total alkaloid fraction in rats. Copyright © 2016 John Wiley & Sons, Ltd.